Integrating eQTL and genome-wide association studies to uncover additive and dominant regulatory circuits in pig uterine capacity - Z. Xu; H. Zeng; J. Teng; X. Ding; J. Li; Z. Zhang (Animal)
Uterine capacity is critical to the economic value of pigs. Exploring the genetic mechanisms that underlie uterine capacity can provide vital insights for pig breeding programmes. Here, we used a mixed model including additive and dominance effects to conduct genome-wide association analysis followed by cross-population meta-analyses for uterine capacity in 8 782 pigs from three pig breeds across nine populations. We identified 192 lead single−nucleotide polymorphisms (SNPs) with additive-specific effects, 236 lead SNPs with dominant-specific effects, and 27 lead SNPs with additive-dominant shared effects. The effects of additive-specific and dominant-specific lead SNPs were shared across breeds to a certain degree. By integrating expression quantitative trait loci, we identified 40 potential dominant-effect and 10 potential additive-effect regulatory circuits, in which a genetic variant affects uterine capacity by modulating the expression of specific gene in specific tissue. For example, rs343882381 affects uterine capacity by regulating the expression of SLC38A10 in the uterus via a dominant effect (PSMR = 7.34 × 10−5, COLOC.PP4 > 0.5), rs337112076 affects uterine capacity by regulating the expression of TNNT1 in the brain via an additive effect (PSMR = 2.36 × 10−35, COLOC.PP4 > 0.5). Our results not only fill the knowledge gap regarding dominant genetic regulation mechanisms of uterine capacity but also provide a key theoretical foundation for the subsequent functional validation and breeding applications.